Molecular analysis of Annexin expression in cancer - Hein, Tobias; Krammer, Peter H.; Weyd, Heiko (BMC cancer, 2022)
Uptake of apoptotic cells induces a tolerogenic phenotype in phagocytes and promotes peripheral tolerance. The highly conserved Annexin core domain, present in all members of the Annexin family, becomes exposed on the apoptotic cell-surface and triggers tolerogenic signalling in phagocytes via the Dectin-1 receptor. Consequently, Annexins exposed on tumour cells upon cell death are expected to induce tolerance towards tumour antigens, inhibiting tumour rejection.